Beyond Expectations: Navigating the Gap Between Anticipated and Realized Collaborative Learning in Higher Education in Nepal - Sharma, Hari Maya (Interdisciplinary Research in Education, 2023)
Collaborative learning is an effective approach in higher education to enhance students’ critical-thinking, problem-solving, and self-regulation skills. However, its implementation remains limited in many Nepalese institutions. In this context, this study aimed to explore the experiences of M.Ed. students of Department of English Education, University, T.U. focusing the gap between anticipated and realized collaborative learning experiences. The qualitative survey design was used for the study and questionnaire were data collection tool. A google form was circulated to 40 Master’s level students via email and the data were thematically analyzed. The findings reveal that while students recognize the potential benefits of collaborative learning, they rarely get the opportunity to participate in such activities during the course cycle. When they do get the chance, they enjoy the opportunities. They advocated for a collaborative learning environment, focusing on preparing students for their future careers as teachers, and seeking equal opportunities for all participants.